THE CONTEMPORARY SLAVE LABOR: ESSAY ON THE NEW CONTENT OF THE ARTICLE 243 OF BRAZILIAN CONSTITUTION FOR THE EFFECTIVENESS OF THE SOCIAL FUNDAMENTAL RIGHT TO DECENT WORK - Nery da Silva, Rogério Luiz; Palma Mattiello, Darléa Carine (Unoesc International Legal Seminar, 2017)
INTRODUCTION This work lies in the study of social fundamental right to decent work and most specifically in the fight against the work in analogous conditions to slavery. From the analysis of the Brazilian constitutional text, its resulting legislative policies and factual statistics data, it is presented, as the central research problem, some possible lacks of forecasts to ensure the so called decent work and the effective efforts to eradicate slave labor in Brazil. This theme is becoming one of the most worldwide debated issues, by the hand of the protective organizations for human rights. Considering the statistical analysis that prove the existence of serious violations of human rights in terms of social fundamental rights to decent work, it is justified the importance of this research,in the contemporary scenario,about the laboring under slavery conditions. In this context, the goal is to analyze the possible protection which can be provided – or its eventual lacks – considering the content of the Constitutional Amendment 81/2014 for the Article 243 of the Federative Republic of Brazil constitution, all in order to clarify whether the new constitutional rules contribute to the effectiveness of the social fundamental right to work, as a guideline for policies launched from the constitutional text against the contemporary forms of slavery. METHODOLOGY It is adopteda comparative form of the deductive method with the help of specialized lawand sociological literature asreferences for quotation and, for sure, the core constitutional text. The research analyzes, initially, the relationship between public policymaking and the enforcement of Constitutional rights, most especially, the social fundamental rights, and so on, to right to work under decent conditions, effort which scrutinizes the notions of contemporary slave labor in opposition to the principle of human dignity. From the released ideas, the work follows studying the new Article 243 of the Brazilian Constitution, in order to raise some solution for the research problem, considering the practice of imposing workers anyrestriction to their freedom as something rude as to suppress their dignity by degrading work with deprivation of liberty. CONTEMPORARY SLAVE WORK, HUMAN DIGNITY AND PUBLIC POLICY In the world and so on, in Brazil as well, since the most ancient times, the main cause of slavery was stated as the economic exploitation – which prevails also in the present time. Contemporary slavery practice manifests itself in the hinding form, marked by authoritarianism, combining the worker's freedom of retrenchment with the violation of their fundamental right to decent work. Contemporaneously, the notion of slave labor is identified by long working hours, paltry salaries, prohibition of circulating, wild discriminations and other precarious threats. Even nowadays, despite of allefforts to the adoption of certain means of protection against thepractice of slave labor, employee is usedto consider some alternatives as “not bad” as others which are even worst. It motivates the acceptation of lots of alternative forms of “job”, in order to find a way of survival. This situation is often found, very frequently in the urban industrial areas, coming to demystify the slave labor binding only with the countryside. For a long time, there existed no effective protection mechanism that workers could use, when subjected to abuse. The work has been related to thestatus of toolfor implementation of human dignity as it happens to its nature as social fundamental right, in accordance with severalcountries’ constitutions. Throughout the long own history, until, in modern times, it is said, even when it is not true. In the Brazilian case, looking forward to follow up on commitments assumed by Brazil upon ratification of Convention No. 29 and 105 and also when the adoption of the ILO Declaration on Fundamental Principles and Rights at Work, ILO launched the Project for Technical Cooperation to Combat Forced (Slavery) Labor in Brazil. This measure sought to promote integrated operations and to strength the actions of all national partner institutions that protect human rights, particularly within the National Commission for the Eradication of Slave Labor, also providing for the rehabilitation of rescued workers to prevent their return to slave labor. In addition, at the Brazilian normative level, the behavior of subjecting someone to conditions analogous to slavery is typified in Article 149 of the Penal Code. In the labor legislation, the provision to rural areas is more than forty years old (Law no. 5,889 / 1973, as amended by Provisional Measure no. 2164-41 / 2001 and Law n. 11,718 / 2008). However, both the question of jurisdiction over the crime as the current setting of the minimum penalty provided for in this article, which is two years, have inhibited any effective prosecution, and there are several favorable devices to the convict that allow to slow down the eventual execution pen. ARTICLE 243 OF THE BRAZILIAN CONSTITUTION CONTEXT AND THE FIGHT FOR ELIMINATION OF CONTEMPORARYSLAVE WORK According to the Ministry of Labor and Employment, it were freed from slavery in Brazil 49,816 people between 1995 and 2015, which seems to be very insufficient numbers to close upwhat to what is estimated to exist. This demonstrates that, despite conveyed policies, slavery work practice has not been eliminated in Brazil. Therefore, legislative measures and other government actions remained being taken, against the continuation of criminal conduct in labor relations, recognized long ago as so offensive to human rights. The issue, therefore, was the subject of most discussion from the issue of Amendment to the Constitution Proposal (PEC) n. 57 from 1999, which was finally, and very lately, approved by the Senate only in 2014, with progress in the House of Representatives under the number 438/2011. The project culminated in the Constitutional Amendment. 81 of June 5, 2014, by which was given new wording to Article 243 of the Constitution, which has been determined that rural and urban properties with illegal plantations of psychotropic plants or slave labor exploitation are expropriated for subsequent allocation to land reform and implementation of public housing programs, without compensation to the owner (BRAZIL, 1988). From the new Constitutional provision, there exists the possibility of applying sanctions of various kinds by the practice of exploitation of slave labor. Noteworthy is the fact that any economic good linked to the forbidden practice can be confiscated, reversing the special fund allocations, under specific legal regulation, when checking exploitation of slave labor. It was instituted, thus, the confiscation of all material linked to the exploitation of slave labor. From this point on, all legal institutions such property are subjected to expropriation under those conditions. Starting from the primary notion that "expropriation" was a genre in which to understand the species "expropriation" and "seizure" (differing, both because there or not payment of a prior compensation to loss of well ownership), one is really facing a confiscation and the state. This is justified by the reason of, as a punitive measure, it could not have any payment as a form of compensation for the economic value lost.It shall be emphasized that, by providing for the loss of property as a penalty to the employer that adopts the slave labor practice, the rule of law clarifies the clear linkage of mutual respect that should exist between the employer and the employee, under penalty of sanctions. The current wording drew attention also to the need of a continued adoption of effective measures in the fight against this practice, which repeatedly occur in national territory, imposing a deep study about the possible forms that forced labor takes in the contemporary era and about the several reactions it causes, in order to mobilize people and garner more support for its eradication. After all, in the twenty-first century, Brazil can no longer affordnor the Brazilian civil society can remain inert about this pernicious violation of the Constitutional principle of human dignity. CONCLUSIONS The wording given to Article 243 of the Brazilian constitution by constitutional amendment No. 81/2014 evaluates the importance of productive men and its working force and consequently the production, to the aggrandizement of economic power. At this point, it remains shown the relevance of the new constitutional provision against the feeling of the exploiters of slave labor, to impart a bias of "reification" to employees which demonstrate the extreme value of "owning" in defeat of the human being respect. Thus, it is expected that the risk of having confiscated their properties (because of badly treating people – as object of their property – will motivate a higher abstention from slavering practice by the land or building owners who act as bad employers. Although this behavior change can, possibly, be adopted only to avoid losing real property that is used slave labor, it creates an opportunity of an effective change in the employing practices and conditions. Therefore the formal existence of legal policies to combat modern-day slavery, if considering the greater reach and relevance they should have, they have not been strong enough to eradicate the practice of labor under those conditions that reduce workers to conditions analogous to slavery and ensure the effectiveness of the fundamental right to decent work. Thus, it is necessary that all information against slave work can reach the appropriately the legal authorities, so that the monitoring shall be effective and the sanctions have to be seriously imposed. The adoption of the measures to combat slave labor with constitutional statusis expected as to enforce government actions to implement and disseminate a greater awareness of civil society with regard to collaboration with complaints and dissemination of eradication campaigns. Thus, the wording given by Constitutional Amendment 81/2014 Article 243 of the Constitution, with the institution of confiscation of properties where slave labor is caught, foreshadows the landscape will suffer some important changes. It looks clear, therefore, that the new constitutional discipline shall contribute to the realization of the social fundamental right to decent work as a barrier to contemporary forms of slavery, allied form, however, other measures. Unfortunately it will not be enough to put an end at this horrible practice. This first effort must be complemented by other measures, if it is considered how the starting point of a job can represent awareness under conditions of greater social vulnerability.It is absolutely imperative to eradicate degrading forms of labor, in compliance with constitutional rules, with greater effectiveness of the social fundamental rights to decent work. [1] Do not take this document as a complete Paper for Discussion. This is merely the format which is supposed to be adopted by authors for submissions to SPRING 2016 | UNOESC INTERNATIONAL LEGAL SEMINAR.